2011
DOI: 10.3155/1047-3289.61.3.238
|View full text |Cite|
|
Sign up to set email alerts
|

Issues with Ozone Attainment Methodology for Houston, TX

Abstract: To comply with the federal 8-hr ozone standard, the state of Texas is creating a plan for Houston that strictly follows the U.S. Environmental Protection Agency's (EPA) guidance for demonstrating attainment. EPA's attainment guidance methodology has several key assumptions that are demonstrated to not be completely appropriate for the unique observed ozone conditions found in Houston. Houston's ozone violations at monitoring sites are realized as gradual hour-to-hour increases in ozone concentrations, or by la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 19 publications
1
11
0
Order By: Relevance
“…A necessary next step is to perform a meteorological analysis similar to the studies described above (Byun et al, 2007;Vizuete et al, 2009). It is important to understand the regional meteorology that was present on NTOC days, because high O 3 in Houston is known to be dependent upon wind fields.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…A necessary next step is to perform a meteorological analysis similar to the studies described above (Byun et al, 2007;Vizuete et al, 2009). It is important to understand the regional meteorology that was present on NTOC days, because high O 3 in Houston is known to be dependent upon wind fields.…”
Section: Resultsmentioning
confidence: 99%
“…These policies are described and justified with modeling and observational data in a document called the State Implementation Plan (SIP) (Texas Commission on Environmental Quality [TCEQ], 2010a), which follows the U.S. Environmental Protection Agency (EPA) attainment methodology (EPA, 2007). The EPA attainment methodology describes the use of observational and modeling data to show attainment, and the assumptions underlying it have been the focus of several studies (Jones et al, 2005;Sistla et al, 2004;Vizuete et al, 2010, Vizuete et al, 2011. Specifically for Houston, researchers have found that the metrics used in the attainment methodology were influenced by large hourly changes in observed O 3 concentrations.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The observed transient high ozone events (THOEs; defined by regulators as monitored ozone increases >40 ppb in 1 hr) were at first thought to be the consequence of routine emissions of highly reactive volatile organic compounds (HRVOCs) from the Ship Channel facilities (e.g., leaks from process vents), together with combustion emissions of nitrogen oxides (NO x ¼ NO þ NO 2 ) and favorable meteorological conditions such as stalled sea breeze fronts and stagnant rotating winds (e.g., Banta et al, 2005). Later, it was hypothesized that flares and other stochastic emission events also contribute to the occurrence of THOEs (Nam et al, 2006;Olaguer et al, 2006), an opinion supported by Vizuete et al (2011), who showed that model simulations of ozone events in Houston based solely on routine point source emissions can only account for broad ozone plumes, as opposed to the narrow ones frequently observed emanating from the Ship Channel.…”
Section: Introductionmentioning
confidence: 99%